The Duration of Unemployment in Russia - Louise Grogan; Gerard J. van den Berg (Tinbergen Institute, 1999)
This paper uses longitudinal survey data to assess factors affecting the duration of unemployment in Russia. We examine four types of marginalised labour force participants, according to ILO guidelines and survey responses, and we estimate duration models for each type. It turns out that the sets of characteristics with the strongest effects on the duration are remarkably similar across the different unemployment definitions and model specifications. Therefore, despite the formidable practical measurement problems, problematic groups of individuals can actually be identified.
Keywords: J61; P20; R23; 330; unemployment duration; job search; Russia; unemployment definition; duration models; Arbeitslosigkeit; Langzeitarbeitslosigkeit; Arbeitsuche; Russland